The Associations of Habitual Intake of Sulfur Amino Acids, Proteins and Diet Quality with Plasma Sulfur Amino Acid Concentrations: The Maastricht Study - Tore, Elena C; Eussen, Simone J P M; Bastani, Nasser E; Dagnelie, Pieter C; Elshorbagy, Amany K; Grootswagers, Pol; Kožich, Viktor; Olsen, Thomas; Refsum, Helga; Retterstøl, Kjetil; Stehouwer, Coen DA; Stolt, Emma T K; et al. (The Journal of nutrition, 2023)
BACKGROUND: Plasma sulfur amino acids (SAAs), i.e., methionine, total cysteine (tCys), total homocysteine (tHcy), cystathionine, total glutathione (tGSH), and taurine, are potential risk factors for obesity and cardiometabolic disorders. However, except for plasma tHcy, little is known about how dietary intake modifies plasma SAA concentrations. OBJECTIVE: To investigate whether the intake of SAAs and proteins or diet quality is associated with plasma SAAs. METHODS: Data from a cross-sectional subset of The Maastricht Study (n = 1145, 50.5% men, 61 interquartile range: [55, 66] y, 22.5% with prediabetes and 34.3% with type 2 diabetes) were investigated. Dietary intake was assessed using a validated food frequency questionnaire. The intake of SAAs (total, methionine, and cysteine) and proteins (total, animal, and plant) was estimated from the Dutch and Danish food composition tables. Diet quality was assessed using the Dutch Healthy Diet Index, the Mediterranean Diet Score, and the Dietary Approaches to Stop Hypertension score. Fasting plasma SAAs were measured by liquid chromatography (LC) tandem mass spectrometry (MS) (LC/MS-MS). Associations were investigated with multiple linear regressions with tertiles of dietary intake measures (main exposures) and z-standardized plasma SAAs (outcomes). RESULTS: Intake of total SAAs and total proteins was positively associated with plasma tCys and cystathionine. Associations were stronger in women and in those with normal body weight. Higher intake of cysteine and plant proteins was associated with lower plasma tHcy and higher cystathionine. Higher methionine intake was associated with lower plasma tGSH, whereas cysteine intake was positively associated with tGSH. Higher intake of methionine and animal proteins was associated with higher plasma taurine. Better diet quality was consistently related to lower plasma tHcy concentrations, but it was not associated with the other SAAs. CONCLUSION: Targeted dietary modifications might be effective in modifying plasma concentrations of tCys, tHcy, and cystathionine, which have been associated with obesity and cardiometabolic disorders.
Keywords: cystathionin; Cross-Sectional Studies; Obesity; cystein; methionin; sulfur amino acids; obezita; Diabetes Mellitus, Type 2; Methionine; diabetes mellitus 2. typu; taurin; dieta; aminokyseliny sírové; kardiovaskulární nemoci; Taurine; homocystein; lidé; ženské pohlaví; proteins; Humans; Cystathionine; průřezové studie; Diet; habitual dietary intake; plasma concentrations; Cardiovascular Diseases; diet quality; Female; Cysteine; Homocysteine; Amino Acids, Sulfur